2017
DOI: 10.1016/j.trsl.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Current approaches for avoiding the limitations of circulating tumor cells detection methods—implications for diagnosis and treatment of patients with solid tumors

Abstract: Eight million people die of cancer each year and 90% of deaths are caused by systemic disease. Circulating tumor cells (CTCs) contribute to the formation of metastases and thus are the subject of extensive research and an abiding interest to biotechnology and pharmaceutical companies. Recent technological advances have resulted in greatly improved CTC detection, enumeration, expansion, and culture methods. However, despite the fact that nearly 150 years have passed since the first detection and description of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 199 publications
(258 reference statements)
2
111
0
1
Order By: Relevance
“…The researchers further observed that patients with CTC levels lower than 5 per 7.5 mL had a higher progression‐free survival and overall survival compared with patients whose CTC levels were above this level. However, one of the limitations of CTC enumeration is that its half‐life in peripheral vascular system is very short (approximately 1‐2.4 hours) before it extravasates into a secondary organ or is actively cleared from the blood . Although the isolation of CTCs from the blood at low levels may be challenging, it has been proven to be beneficial as a tool to predict prognosis in cancer patients and thus should be subjected to further research …”
Section: Liquid Biopsy Componentsmentioning
confidence: 99%
“…The researchers further observed that patients with CTC levels lower than 5 per 7.5 mL had a higher progression‐free survival and overall survival compared with patients whose CTC levels were above this level. However, one of the limitations of CTC enumeration is that its half‐life in peripheral vascular system is very short (approximately 1‐2.4 hours) before it extravasates into a secondary organ or is actively cleared from the blood . Although the isolation of CTCs from the blood at low levels may be challenging, it has been proven to be beneficial as a tool to predict prognosis in cancer patients and thus should be subjected to further research …”
Section: Liquid Biopsy Componentsmentioning
confidence: 99%
“…At present, various technologies are developed for CTCs isolation, however, they are mainly used for research purposes rather than clinical applications (Bankó et al, 2019). Among the obstacles are the presence of ITH (Levitin et al, 2018;Lim et al, 2019), limited knowledge on CTCs mechanism of action in cancer progression (shedding from the primary/metastasis tumor, survival in bloodstream, avoidance of apoptosis, colonization potentials and settlement in distant organs), the rarity of CTCs (0 to 10 CTCs/ml whole blood in 30% to 50% mCRC patients) (Zieglschmid et al, 2005), various sizes of CTCs and the lack of clinical validation (Millner et al, 2013;Rejniak, 2016;Kowalik et al, 2017;Bankó et al, 2019). In addition, there are only a few studies relating to CTCs pharmacogenomics and underlying survival mechanisms (Wang et al, 2018) as well as the cell-cell interactions in CRC microenvironment (Krog and Henry, 2018), and majority of them are based on experimental and theoretical extrapolations (Burz et al, 2018).…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…• circulating tumor cells, 13,14 • circulating extracellular nucleic acids, including cell-free DNA (cfDNA), mRNA, and microRNA (miRNA), 7,15 • extracellular vesicles (e.g., exosomes), 16,17 • nucleosomes, 18,19 • various glycoproteins and antigens (e.g., PSA, CEA, CA 125, CA19-9, βHCG, αFP, etc.). 3,4 Although all these components of liquid biopsies have advantages and limitations (for reviews, see refs.…”
Section: Introductionmentioning
confidence: 99%